EVOLUTIONARY STABLE STRATEGY DALAM PERMAINAN EVOLUSIONER PADA PERILAKU HEWAN - , MARATUS KHASANAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final project discusses about evolutionary games. One of game theory application learning about evolution of animal behavior. Using a game theory application, we can improve understanding of the animal behavior from generation to generation. The concept of an Evolutionary Stable Strategy (ESS) is defined and its consequences are explored in two or three person games. The basic idea of the development of game evolution are made by showing some examples of contest between animals in the wild. If all the population of animals are using a certain strategy, then it does not pay some to change to a different. It is not assumed that animals could easily change strategy, because there is only a genetic mutation which could produce mutant strategy. Some examples will be added to make it easier to understand the main idea.